Combination of second generation feedstocks as a strategy for bacterial endoglucanase production / Oke Mushafau Adebayo - Oke, Mushafau Adebayo (2016)
Environmental concerns and the instability associated with the use of fossils as sources of fuel and platform chemicals have prompted interest in the use of biomass as alternatives. Lignocellulosic biomass is cheap and abundant but its use is yet to be adopted widely because of the expensive processing requirements. Cellulases, enzymes required for the conversion of lignocellulosics into useful products, are very expensive because they are produced from purified commercial substrates. Researchers have thus explored the use of lignocellulosic substrates as cheaper alternatives. Efforts have so far focused mainly on the production of fungal cellulases from single feedstocks while the use of mixed feedstocks have been poorly explored, especially for bacterial cellulases. This project sought to investigate the feasibility of mixed lignocellulosic feedstocks application as a strategy for improving the production of bacterial endoglucanase, a cellulase type with wide industrial applications. A sequential screening approach was used in selecting a bacterial strain that could efficiently utilize a mixture of oil palm empty fruit bunch (EFB), oil palm frond (OPF) and rice husk (RH) for endoglucanase production. Endoglucanase production ability of this strain on the single- (SS) and mixed substrates (MS), as well as on synthetic cellulosic substrates, was investigated. The possibility of reducing media supplementation cost by evaluating some agro-industrial wastes as supplements or substitutes to selected media components was explored. The effects of substrate pretreatment were also studied in order to identify an ideal pretreatment method conducive for enzyme production. The efficiency of joint/separate pretreatments and combination of the single substrates against their separate use for endoglucanase production was investigated. Response surface method (RSM) was applied in the optimization of selected fermentation process variables and substrate component proportions for maximum endoglucanase yield. iv The first documentation of cellulolytic ability in a Bacillus aerius strain was presented in this study. This strain produced significantly higher yields of the enzyme on sequentially-pretreated MS than on the SS and synthetic substrates. Leucaena leucocephala (Petai belalang) as a medium supplement, increased endoglucanase production significantly compared to the control. Pretreatment studies showed that there was no significant difference in enzyme production between the pretreated and untreated MS. Higher pretreatment severity was detrimental to endoglucanase production. Pretreating the SS jointly favoured enzyme production than separate pretreatment approach. Combination of the SS had no negative effects on endoglucanase production. EFB showed a stronger effect towards enzyme production than the other mixture components. RSM optimization revealed that medium pH of 7.45, 184.8 rpm agitation speed, and 37 °C temperature were the most suitable conditions for endoglucanase production. Mixture designs showed that MS with higher amounts of EFB favoured enzyme production. The study demonstrated that mixed feedstock strategy could help to realize enhanced and cost-effective production of B. aerius endoglucanase, provided that carefully selected, mildly pretreated mixture components, at appropriate ratios, and at optimal fermentation conditions are used. The study also provided insights into some aspects of B. aerius cellulolytic system that were previously unreported.